2017
DOI: 10.4335/15.1.43-66(2017)
|View full text |Cite
|
Sign up to set email alerts
|

Do Political Factors Affect the Risk of Local Government Default? Recent Evidence from Spain

Abstract: High levels of debt, provoked by a situation of economic and financial crisis, constitute a major threat to the financial sustainability of governments in the euro zone and in many other parts of the world. This delicate state of public finances also affects local governments and has led researchers to study the variables that influence the volume of bank debt. However, few have specifically analysed the causes of local government default, although it has provoked spending cutbacks and tax increases in many co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…In turn, authors like Amanatullah et al (2010) found evidence of different management styles between men and women and as a consequence, different outcomes and performances. -Galera et al (2017), however, found that the mayor's gender was not a statistically significant factor in the risk of local government default. In light of the differences in management behaviour between men and women, in this study we analyse whether there are differences in local government management that may be attributed to the gender of the governing leader.…”
Section: Gender Of the Mayor (Gen)mentioning
confidence: 84%
See 4 more Smart Citations
“…In turn, authors like Amanatullah et al (2010) found evidence of different management styles between men and women and as a consequence, different outcomes and performances. -Galera et al (2017), however, found that the mayor's gender was not a statistically significant factor in the risk of local government default. In light of the differences in management behaviour between men and women, in this study we analyse whether there are differences in local government management that may be attributed to the gender of the governing leader.…”
Section: Gender Of the Mayor (Gen)mentioning
confidence: 84%
“…It is therefore of interest to analyse how this change in the legislation might have affected compliance with the restrictions established in the LOEPSF. In this vein, Navarro-Galera et al (2017) found that having a higher proportion of women councillors helps to reduce the risk of local governments failing to meet their financial obligations. Geys and Revelli (2011) observed a positive relationship between the number of women councillors and the combination of tax revenues in municipalities.…”
Section: Percentage Of Women Councillors (Counc)mentioning
confidence: 99%
See 3 more Smart Citations